2014
DOI: 10.1007/s10522-014-9506-3
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Werner syndrome protein (WRN): relationships with DNA damage, DNA replication and DNA metabolic activities

Abstract: Loss of WRN function causes Werner Syndrome, characterized by increased genomic instability, elevated cancer susceptibility and premature aging. Although WRN is subject to acetylation, phosphorylation and sumoylation, the impact of these modifications on WRN’s DNA metabolic function remains unclear. Here, we examined in further depth the relationship between WRN acetylation and its role in DNA metabolism, particularly in response to induced DNA damage. Our results demonstrate that endogenous WRN is acetylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that apoptosis-associated genes are dysfunctional in mice lacking Wrn protein 54 . In the meantime, we found more γH2AX signals appeared in wrn zebrafish at early developmental stage, indicating the loss of wrn caused DNA damage, which could be one of the plausible explanations that why loss of wrn caused apoptosis 55 . Microinjection of human WRN mRNA into the one-cell stage of wrn −/− mutant embryos could facilitate chondrocyte proliferation and increase total body length, indicating that WRN is crucial for chondrocyte growth development.…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that apoptosis-associated genes are dysfunctional in mice lacking Wrn protein 54 . In the meantime, we found more γH2AX signals appeared in wrn zebrafish at early developmental stage, indicating the loss of wrn caused DNA damage, which could be one of the plausible explanations that why loss of wrn caused apoptosis 55 . Microinjection of human WRN mRNA into the one-cell stage of wrn −/− mutant embryos could facilitate chondrocyte proliferation and increase total body length, indicating that WRN is crucial for chondrocyte growth development.…”
Section: Discussionmentioning
confidence: 65%
“…Cells expressing a WRN variant that is mutated at the six lysine residues thereby blocking its acetylation are hypersensitive to MMC, suggesting that an important aspect of WRN’s role in the DNA damage response is its regulation by acetylation which prevents its proteolytic degradation via a ubiquitin-proteasome pathway. Thus WRN acetylation and deacetylation may serve as a switch during DNA damage conditions that influences WRN catalytic function or its own degradation which in turn alters its role at stalled replication forks or sites of DNA damage [ 69 ]. In the future, it will be valuable to assess if certain histone deacetylase (HDAC) inhibitors currently used in the clinic might affect the acetyltransferase that modifies WRN as it is known that this class of compounds can alter the acetylation state and function of non-histone proteins as well as their traditional histone targets [ 70 , 71 , 72 ].…”
Section: Acetylation Of Werner Syndrome Helicase (Wrn) Regulates Imentioning
confidence: 99%
“…Acetylation modication plays a key role in the regulation of DNA repair and acts on many DNA repair related proteins. [39][40][41] SIRT1 is identied as one of the major deacetylases to catalyze this process. For example, SIRT1 deacetylated WRN at 6 lysine residues, promoting its translocation from nucleoli to the damage foci when DNA was impaired by cytotoxic substances, thus inhibiting its degradation.…”
Section: Discussionmentioning
confidence: 99%